2020
DOI: 10.1186/s40101-020-00241-x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory fitness is strongly linked to metabolic syndrome among physical fitness components: a retrospective cross-sectional study

Abstract: Background Maintaining a good level of physical fitness from engaging in regular exercise is important for the treatment and prevention of metabolic syndrome (MetS). However, which components constitutive of physical fitness confer the greatest influence remains controversial. This retrospective cross-sectional study aimed to investigate the association between MetS and physical fitness components including cardiorespiratory fitness, muscle strength, flexibility, and agility and to identify which physical fitn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
1
8
0
1
Order By: Relevance
“…One of the main findings of this study was that low CRF increased the ORs for MetS up to 3.5 and 3.7 times in men and women, respectively. These results are in agreement with those of previous studies [26,27]. In a meta-analysis of 33 studies, an increase in CRF by 3.5 mL/kg/min decreased mortality and morbidity from cardiovascular disease by 13% and 15%, respectively [28].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…One of the main findings of this study was that low CRF increased the ORs for MetS up to 3.5 and 3.7 times in men and women, respectively. These results are in agreement with those of previous studies [26,27]. In a meta-analysis of 33 studies, an increase in CRF by 3.5 mL/kg/min decreased mortality and morbidity from cardiovascular disease by 13% and 15%, respectively [28].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the prevalence of MetS was 5.4% in men with high CRF and 13.9% in those with low CRF [27]. In a subsequent analysis with CRF in which the risk for MetS was evaluated per quartile, it was found that the lowest quartile group exhibited a 3.6-fold higher risk than the highest quartile group [26]. A representative strategy to improve CRF is to continuously perform moderate-intensity aerobic exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The Mann–Whitney U test was used for non-normally distributed data that were verified by utilizing Levene’s test for equality of variances. The Jonckheere–Terpstra test was used to identify trends in parameters among the three groups (two-tailed) [ 29 , 30 , 31 , 32 , 33 ]. This test generated standardized statistics that represented the strength of trends in parameters that increased or decreased across groups [ 29 , 30 , 31 , 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Jonckheere–Terpstra test was used to identify trends in parameters among the three groups (two-tailed) [ 29 , 30 , 31 , 32 , 33 ]. This test generated standardized statistics that represented the strength of trends in parameters that increased or decreased across groups [ 29 , 30 , 31 , 32 , 33 ]. Logistic regression was employed to evaluate the relationships of the TyG index, which was an independent parameter, with obesity, sarcopenia, and sarcopenic obesity, which were dependent parameters.…”
Section: Methodsmentioning
confidence: 99%
“…Data that were not normally distributed were compared between groups using the Mann–Whitney U test. The Jonckheere–Terpstra test (two-tailed) was utilized to generate standardized statistics allowing comparison of trends among the three groups [ 19 , 29 , 33 , 34 ]. p -values < 0.05 were considered significant in these analyses.…”
Section: Methodsmentioning
confidence: 99%